International Classification of Diseases, Tenth Revision Implementation: Is the Workforce Ready?. Issue 1 (January 2018) - Sacconi, Patricia; Glover, Pamela; Marriot, Robert; Paul, David P.; Coustasse, Alberto
Abstract : After many delays, the United States finally implemented the International Classification of Diseases, Tenth Revision, Clinical Modification/Procedural Coding System on October 1, 2015, bringing the United States into line with other industrialized nations, most of which had been using the International Classification of Diseases, Tenth Revision for many years. We outline the benefits and challenges to the preparatory activities of the International Classification of Diseases, Tenth Revision, Clinical Modification/Procedural Coding System implementation for the US health care industry. To ease the transition, the Centers for Medicare & Medicaid Services allowed health care facilities to submit test claims prior to the implementation date and delivered feedback on the acceptability of those claims. Early results indicated a relatively smooth transition, although some questions regarding the available data remain. Additional data, especially data concerning outcomes, are required.